2023
DOI: 10.3390/rs15123062
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Monitoring and Analysis of Reservoir Dams Based on SBAS-InSAR Technology—Banqiao Reservoir

Abstract: Most dams in China have been operating for a long time and are products of the economic and technical limitations at the time of construction. Due to decades of aging engineering and ancillary problems, these reservoirs pose great threats to the safety of local people and the development of the surrounding economy. In this study, the surface deformation information for the Banqiao Reservoir is monitored with the small baseline subset–synthetic aperture radar interferometry (SBAS-InSAR) method using 80 Sentinel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The results obtained through PSInSAR were consistent with traditional geodetic methods and GNSS measurements. Additionally, Pang et al (2023) confirmed the effectiveness of SBAS-InSAR technology in studying vertical displacements of the Banqiao Reservoir Dam surface in China between 07/03/22 and 08/20/22. The dam displacement fluctuated between 4 to -8 mm, with the largest deviations between InSAR and GNSS (BeiDou) monitoring values being 2 mm.…”
Section: Page Layoutsupporting
confidence: 61%
“…The results obtained through PSInSAR were consistent with traditional geodetic methods and GNSS measurements. Additionally, Pang et al (2023) confirmed the effectiveness of SBAS-InSAR technology in studying vertical displacements of the Banqiao Reservoir Dam surface in China between 07/03/22 and 08/20/22. The dam displacement fluctuated between 4 to -8 mm, with the largest deviations between InSAR and GNSS (BeiDou) monitoring values being 2 mm.…”
Section: Page Layoutsupporting
confidence: 61%
“…The SBAS-InSAR method [21], as a representative time series InSAR technique, effectively overcomes the effects of temporal and spatial decorrelation and atmospheric delays by appropriately combining interferograms to analyze distributed scatterers (DSs) with high coherence. Research results from the application of SBAS-InSAR technology in dam monitoring [22][23][24] demonstrate that this technique can efficiently and accurately obtain deformation monitoring results for dams, allowing for real-time assessment of the dams' operational health status.…”
Section: Introductionmentioning
confidence: 99%
“…In 1959, the Malpasset arch dam in France burst due to the instability of the dam shoulder, causing a huge loss of life and property [9]. Since a strong dam can reduce the downstream impact of landslides and rapid changes in water levels, it can be said that dam safety is related to the safety of downstream people's lives and production [10]. As an important indicator for evaluating dam safety, it is necessary to carry out the comprehensive and regular deformation monitoring of dams.…”
Section: Introductionmentioning
confidence: 99%